Unlocking AI's Potential in Language Learning: A Comparative Study of Adoption and Effectiveness in Indonesia and Arab Countries - Fina Septia; Tamer Sa’ad Ibrahim Khodr; Abdullah; Nushrotul Ilah (WISE Pendidikan Indonesia, 2024)
This study examines the differences in the adoption and effectiveness of artificial intelligence (AI) in language learning between Indonesia and Arab countries. Using a quantitative comparative approach, data were collected from 200 educational institutions across both regions. The findings reveal significant disparities in AI adoption, with Arab countries showing a higher level of integration and effectiveness compared to Indonesia. This is attributed to better technological infrastructure, stronger policy support, and more comprehensive teacher training programs in Arab countries. In contrast, Indonesia faces challenges such as limited access to technology and less comprehensive AI integration, which impact the effectiveness of AI in enhancing language skills. The study suggests that for AI to deliver maximum benefits in language learning, a holistic approach is necessary, including investments in infrastructure, extensive teacher training, and fostering a more innovative educational culture. The findings provide valuable insights not only for Indonesia and Arab countries but also for other nations seeking to integrate AI into their educational systems.